ANALYSIS OF THE ROMANIAN PENSION SYSTEM FROM AN EUROPEAN - VIRJAN DANIELA (Annals of the University of Oradea: Economic Science, 2009)
The political, economic, social, cultural and especially demographic aspects have put their inprints on the pension, so that it should keep in mind the way they were built and are building the European social policies in general, and EU policy on pensions